Factors Related Oral and Dental Health Care Behaviors among Soldiers in Udonthani Province - Panyathorn, Kanchana; Butsaenlee, Supaya; Kaewkullaya, Kanittha; Sukatungka, Krittika (Journal of The Royal Thai Army Nurses, 2023)
The purpose of this cross - sectional analysis research was to identify factors related oral and dental health care behaviors among the soldiers. The sample consisted of 338 soldiers working in Udon thani province. The research instruments comprised of questionnaires that measured the attitude, health beliefs, and health care behaviors of the soldiers with a Cronbach’s alpha coefficient of .892, .851, and .911, respectively. The data was analyzed by using descriptive statistics, Chi-square, Pearson’s correlation and stepwise multiple regression. The results show that the soldier’s attitude toward oral and dental health care was at a high level ( 4.19, S.D.732). Additionally, the overall perception of health beliefs was also at high level ( 4.21, S.D. 597), as was their oral and dental health care behavior ( 4.44, S.D.832). Factors related oral and dental health care behaviors of the soldiers were service age, marriage status, income, attitude, perceive of health believes and advise receiving from health personal. Multiple regression analysis showed service age, attitude and perceived of health believes could all together predict 54.5% of oral and dental health care behaviors (R2 = .545). From the results of this study, it was suggested that the relevant agencies should provide activities that serve to develop the attitudes and health beliefs of the soldier, and work to develop the quality of oral and dental health care service system.